2017
DOI: 10.14254/2071-789x.2017/10-1/19
|View full text |Cite
|
Sign up to set email alerts
|

The Inequality of Material Living Conditions in EU Countries

Abstract: ABSTRACT. Socio-economic inequality has become one of the most relevant problems in the global economy. Studies carried out in the past 10 years have revealed that a high level of inequality prevents economic growth. The standard means of measuring these differences in equality include methods and aspects such as looking at inequalities in income and consumption, but these criteria do not reflect the actual level of inequality. To find out the actual level of socio-economic inequality, the distribution of weal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Studies carried out in the past 10 years have revealed that high level of inequality prevents economic growth (Pernica, 2017). Nevertheless, as stated by (Rakauskienė & Volodzkienė, 2017), in order to study the actual level of socioeconomic inequality, we need to consider the distribution of wealth in different aspects. For this reason, they analysed the distribution of material living conditions and housing inequality in Lithuania and other EU countries, with a special focus on the extent and volatility of the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies carried out in the past 10 years have revealed that high level of inequality prevents economic growth (Pernica, 2017). Nevertheless, as stated by (Rakauskienė & Volodzkienė, 2017), in order to study the actual level of socioeconomic inequality, we need to consider the distribution of wealth in different aspects. For this reason, they analysed the distribution of material living conditions and housing inequality in Lithuania and other EU countries, with a special focus on the extent and volatility of the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, scientists emphasize that the differentiation of incomes, especially when compared with existing proportions in neighbouring countries, becomes a significant migration driver, under the influence of which the demographic situation is becoming deteriorated and the perspectives of human capital reproduction are becoming more complicated in low-welfare countries, Ukraine being one of them [2]. At the same time, not only in developing countries, but also in developed ones, inequality is a fact recognised by scientists as a largely constraining social and economic progress and predetermines the imbalances of regional development [3][4][5]. In this case, one of the most famous works in the field of study of inequality and possibilities of its eradication, grounded by Doyle, M.W.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of Khan et al (2016) and Li & Huang (2009), it was proved that a co-integration connection between health and education has positive effects on the economic growth. The effect of the health status of the population can also be found in other economic and social aspects, such as countries' innovation performance (Herzer, 2020;Pacáková & Kopecká, 2019), knowledge transfer (Bar & Leukhina, 2010), technological progress (Gehringer & Prettner, 2019;Lechman, 2019), labour supply ( Jiang et al, 2019), and poverty (Kim, 2018;Rakauskienė & Volodzkienė, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%